Preserving Meaning and Context: A Study of Cultural Adaptation in the Translation of Arabic Proverbs - Zaki Ghufron; Subhan Subhan; Mufrodi Mufrodi; Azizah Alawiyyah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This research delves into the intricate dynamics of translating proverbs, aiming to ensure that the essence of the source language is accurately conveyed in the target language. Translating proverbs presents unique challenges due to the inherent cultural and contextual nuances embedded within them. To address this, employing culturally equivalent strategies becomes crucial in faithfully representing the intended meaning. The process of translating through culture is not merely a mechanical task; it serves as a bridge fostering a profound understanding between different cultures. This bridge facilitates the effective communication of proverbial messages in the target language, exemplified by the proverb